Contested and Uncontested Religious Landscape Markers: The Dissemination of Crosses in Northern Albania (1990-2020) - Muhaj, Ardian; Beqa, Mentor (Context: Journal of Interdisciplinary Studies, 2022)
This paper analyses the relationship between the “politics of religious symbolism” and the physical landscape of post-communist Albania. It examines the proliferation of crosses on highly visible peaks, especially in Northern Albania where both Muslims and Catholics live. The paper combines qualitative and quantitative methods to understand the basis of this phenomenon, and conducts field interviews to reveal the exclusivist nature of Catholicism as its main driving factor. While most Catholics believe this exclusivity is their right, many Muslims feel provoked by attitudes they describe as offensive. Although the phenomenon has been marginalised from national public debate under the auspices of “religious tolerance”, the tension it has created is very much present.